On The Expression Of Terrorism In Moore: Analysis Of Neologisms - Issoufou François TIROGO (Akofena)
Abstract: This study deals with the lexicon of terrorism in Moore, a Gur language spoken in Burkina Faso, West Africa. This country has experienced recurrent terrorist attacks since 2015. As part of the fight against this scourge, communication in Moore encounters certain difficulties when it comes to naming new concepts. The aim of this study is to examine the processes used in lexical creation to express the concept of terrorism in this language. Based on documentary research and interviews with media professionals, the analysis reveals that the names proposed for terrorism in Moore are compound words. Among these constructed words, the most productive are exocentric compounds, in this case lexicalized phrases. These are processes of semantic innovation, which are manifested in naming by description.